Unsteady magnetohydrodynamics nano fluid flows past a cut magnetic solid sphere when the mix convection included. Issue 1 (May 2021) - Widodo, B
Abstract: The system of engine in a car is one of the magnetohydrodynamic (MHD) implementations. This system applies the basic concept of MHD, which is fluid motion that can conduct electric current because of a magnetic field. Several researchers therefore commenced to develop these ideas by observing the characteristics of the numerical simulation solutions. Because of the significance of this research, we are interested in assessing the effect of forced convection on MHD fluid flow, especially nano-fluids, when passing over a magnetic object. We therefore consider the MHD analysis of nano-fluids through sliced magnetic spheres that are induced by mixed convection problem using a mathematical model. This mathematical model is developed from the continuity equation, the momentum equation and the energy equation. The model is then elucidated numerically by means of the finite difference method with the Keller-Box scheme and MATLAB software. Furthermore, within numerical simulations investigated the effects of magnetic parameters (M), slice angle parameters (θs ), and volume fraction of nano-fluid (X) towards fluid velocity and temperature. The numerical solutions express that when the magnetic parameter (M) rises, the velocity of the nano-fluid drops and the temperature of the nanofluid growths. When the cut angle parameter (θs ) enlarges, the velocity of the nano-fluid enhances and the temperature of the nano-fluid lessens. When the volume fraction of nanofluid (X) expansions, the velocity of the nano-fluid falls and the temperature of the nanofluid rises.